The strategic perspective for the execution of judgments of the European Court of Human Rights - Sedrakyan, Artyom (Bulletin of Yerevan University C: Jurisprudence, 2023)
Strategic aspects of execution of the European Court of Human Rights judgments are analyzed in this article. In the author’s view, a strategic perspective matters also for the execution of judgments; State agencies should be armed with the ability to anticipate, prepare, and get positioned for further challenges. He suggests that there is an objective need to ensure the responsible involvement of relevant state bodies in the process of execution of judgments, clarifying the toolkit of interaction between them. With this view, several strategic steps are highlighted. The author concludes that the adoption of a national strategy for interaction will increase the understanding of “shared responsibility” among state institutions within the process of the execution of judgments of the Strasbourg Court